Continental-scale behavioral response of birds to a total solar eclipse - David Mann; Austin Anderson; Amy Donner; Michael Hall; Stefan Kahl; Holger Klinck (Scientific Reports)
Abstract Based on anecdotal evidence and research involving human observation and community science, radar analyses, and acoustical studies, birds are thought to stop singing and engage in nighttime behaviors such as roosting during a total solar eclipse. However, these research methodologies are limited by small sample sizes, potential effects of human observation altering birds’ behaviors, and biases in human-recorded findings. Here we show how a community science network of bioacoustics devices using machine learning revealed a decrease in bird vocalization across North America at sites which experienced more than 99% maximum solar obscuration during the total solar eclipse on April 8, 2024. There was variability between sites in bird vocalization responses to a solar eclipse after controlling for human presence. A widely distributed, connected, and automated passive acoustics monitoring system will allow research into the impact on wildlife of wide spatiotemporal, continental-scale events including wildfires and extreme weather events.